Berbamine as potential STING inhibitor For KRAS-mutant non-small cell lung cancer - Haoxin Yan; Jumin Huang; Yuwei Wang; Yizhong Zhang; Wenkang Ren; Zhiran Zhai; Yuping Tang; Huanling Lai; Xingxing Fan; Lihua Liu; Elaine Lai-Han Leung (Pharmacological Research)
Lung adenocarcinoma (LUAD) is a leading cause of cancer-related mortality. Poor prognostic results in LUAD are frequently associated with KRAS mutations and drug resistance. KRAS mutations can induce STING activation by triggering DNA damage response (DDR) activation. This persistently activated STING signaling gives rise to an immunosuppressive microenvironment, thereby complicating treatment efforts. In this study, we identified that the low-toxicity pro-apoptotic drug Berbamine (BBM) as a potential therapeutic agent for LUAD cells with KRAS mutations. BBM exhibits anti-tumor effects by triggering cell cycle arrest, enhancing senescence, and activating apoptosis. BBM also targets STING, leading to the downregulation of p-STING (Ser366) and CCL2. This in turn reduced the infiltration of M-MDSCs into the tumor microenvironment. These combined mechanisms not only suppress STING-dependent tumor growth but also remodel the immunosuppressive tumor microenvironment, thereby enhancing anti-tumor immunity. Collectively, our findings position BBM as a promising therapeutic agent for LUAD with KRAS mutations, offering a strategy to target STING-associated pathways, overcome immune suppression, and ultimately improve patient outcomes.